Research in Consumer Preferences Selecting the Services of Wellness-Fitness Centres in Kaunas - Vilma Tamulienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Competition among wellness-fitness centre companies is quite high. Each company which provides services to sport, in order to effectively carry out its activities, must take into account not only the political, economic, social, cultural, technological environment to follow current and potential competitors and their actions, but also consumer needs and priorities in selecting services. In addition, wellness-fitness centre managers must know the key criteria of consumer choice, especially when preparing strategic marketing plans for future company activities. Hypothesis - the most important keys of consumers selecting fitness centres services are geographic location, the quality of services and price. Research aim was to determine consumer preferences in selecting fitness and wellness services at the largest health centres in Kaunas. Research methods. The methods of quantitative questionnaire survey and observation were used, as well as the comparison of the conducted research findings with Euro barometer (2009), "Rait" (2007), KTU representatives investigating  the  customers  in  "Impuls"  sports  and  entertainment  parks  (2009),  Lithuanian  Union  of  Sports Federations (LSFS) in 2010. The questionnaire survey was conducted in March-April of 2011. A random probability sampling method was used with visitors (n = 170) from four largest wellness-fitness centres in Kaunas and the e-version of the questionnaire was uploaded into the social network profiles of wellness-fitness centres. The data were analysed and processed using statistical package for social sciences (SPSS 17.0 version). Research results. Results of the present research allow concluding that respondents' opinions concerning the following service assessment of wellness-fitness centres in Kaunas were very scattered and very unequal (standard deviation of the motivator assessment >1). However, only one provided service coincided. It was the service of sauna and sauna area (standard deviation of the motivator assessment = 0.996 < 1). The research hypothesis was proved partially. Discussion and conclusions. Having executed the research it was determined that there were very versatile consumer priorities in selecting the service provided by wellness-fitness centres in Kaunas and it was impossible to distinguish predominant ones proving that wellness-fitness centres had to focus on the personalized service packages and modern information technologies for the customer relationship management. Keywords: consuming sports services, companies of sports services, package of services.